Pengembangan Media Pembelajaran Digital Menggunakan Aplikasi Canva pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar - Siregar, Safwina Rizayani; Iraqi, Hana Shilfia; Zuardi, Zuardi; Syafitri, Serly (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop a valid, practical, and effective digital learning media based on Canva for teaching IPAS in fourth grade elementary school that can be used in the learning process. This type of research is development research (Research and Development) with the ADDIE development model. The trial subjects were conducted at UPTD SDN 35 Hutagodang, followed by research at UPTD SDN 02 Hutagodang, and then implemented at UPTD SDN 16 Hutagodang. The results of the development research of digital learning media based on Canva in IPAS learning for grade IV elementary school are valid with an average of 86.33% in the "Very Valid" category. For the practicality results from teachers and participants in the trial school, the average percentage is 94% in the "Very Practical" category. In the research school, the average percentage is 96.64% also in the "Very Practical" category. Meanwhile, at the implementation school, the average percentage is 98.10% in the "Very Practical" category. The effectiveness test at the trial school produced a result of 70% in the "High" category. In the research school, the results were 88% with the category 'Very High'. Meanwhile, in the implementation school, the results were 95% with the category 'Very High'. Based on these research results, it can be concluded that digital learning media based on IPAS learning in the fourth grade of elementary school is declared valid, practical, and effective for use and can be an alternative solution for innovative and engaging learning media for students.